Accounting Based Governance and Intellectual Capital on CSR Disclosure: A Legitimacy Theory Approach - Ryani Kusumawati, Retno; Sulistiana, Indra (Inovasi Analisis Data, 2025)
Objective: This study examines the influence of corporate governance (CG), intellectual capital efficiency (ICE) and earnings quality (EQ) on the quality of CSR disclosure. It also examines the moderating effect of EQ in the relationship between CG and CSR disclosure in the mining industry.Methods: This study applies a quantitative method by conducting analysis over panel data of 140 mining sector companies listed on the Indonesia Stock Exchange from 2020 until 2024. The variables were quantified using documentation methods informed by financial reports and sustainability disclosures. The hypotheses were analyzed through MLR, incorporating interaction terms to study moderation effects.Results: It is found that CG, ICE, and EQ are positively and significantly associated with CSR disclosure. In addition, EQ behaves as a moderator in enhancing the impact of CG on CSR disclosure, which provides evidence that companies with high EQ have stronger governance-based CSR disclosure.Novelty: In contrast to prior studies that consider these variables separately, this research introduces earnings quality as a moderator to obtain a more holistic stance to understand the way governance and financial reporting quality interplay on sustainability disclosure practices in an emerging market.Research Implications: These findings yield valuable empirical information for regulators and company participants to strengthen the governance structure and financial transparency as ways to promote CSD disclosure as two complementary policies at work. This research also underlines the relevance of linking CSR policies with internal financial quality indicators.